2019
DOI: 10.3892/etm.2019.8389
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive components from garlic on brain resiliency against neuroinflammation and neurodegeneration (Review)

Abstract: Garlic (Allium sativum) has been widely used for culinary and medicinal purposes. Aged garlic extract (AGE) and sulfur-containing compounds, including S-allylcysteine (SAC) are well documented botanical active components of garlic. AGE is prepared by the prolonged extraction of fresh garlic with aqueous ethanol and is considered a nutritional supplement with potential to promote human health. SAC is a water-soluble organosulfur compound and the most abundant component of AGE. Studies have demonstrated that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Administration of GO (46 mg/ kg body weight) markedly attenuated impaired short-term memory and motor coordination after global cerebral ischemia for 10 min followed by reperfusion for 24 h in mice (Gupta, Singh, and Sharma 2003). A recent study reported that the neuroprotective effect of garlic could be attributed to organosulfur components (Song et al 2020). SAC down-regulated hippocampal nuclear NF-κB and attenuated oxidative stress, resulting in mitigating cognitive deficits (Zarezadeh et al 2017).…”
Section: Garlic (Allium Sativum)mentioning
confidence: 98%
“…Administration of GO (46 mg/ kg body weight) markedly attenuated impaired short-term memory and motor coordination after global cerebral ischemia for 10 min followed by reperfusion for 24 h in mice (Gupta, Singh, and Sharma 2003). A recent study reported that the neuroprotective effect of garlic could be attributed to organosulfur components (Song et al 2020). SAC down-regulated hippocampal nuclear NF-κB and attenuated oxidative stress, resulting in mitigating cognitive deficits (Zarezadeh et al 2017).…”
Section: Garlic (Allium Sativum)mentioning
confidence: 98%
“…AGE and FruArg can reduce neuroinflammatory reactions via a variety of signaling pathways, including Toll-like receptor and interleukin (IL-6) signaling, as well as upregulation of the nuclear factor erythroid 2-related calculate 2 (Nrf2)-mediated oxidative stretch pathways, which have been shown to improve microglial resistance to neuroinflammation and neurodegeneration. FruArg's capacity to cross the blood-brain barrier (BBB) suggests that it could be used as a medicinal drug [78]. DADS and DATS were found to have neuroprotective properties.…”
Section: Neuroprotectivementioning
confidence: 99%
“…It is known that onion, garlic, grapes, rosemary, broccoli, spinach, turmeric, parsley, etc., possess considerable antioxidant activities [38,40] and prevent several neurodegenerative diseases including AD [41]. For example, the odorless aged garlic extract (AGE) contains antioxidant chemicals that prevent oxidative damage [42]. AGE has been shown to protect against cellular damage that occurs due to the accumulation of β-amyloid peptide (Aβ) in vitro and to counteract the toxicity of Aβ [42].…”
Section: Nutraceuticals: Overviewmentioning
confidence: 99%
“…For example, the odorless aged garlic extract (AGE) contains antioxidant chemicals that prevent oxidative damage [42]. AGE has been shown to protect against cellular damage that occurs due to the accumulation of β-amyloid peptide (Aβ) in vitro and to counteract the toxicity of Aβ [42]. Furthermore, always in relation to AD pathogenesis, AGE can reduce the hyperphosphorylation of tau protein by modulating the activity of glycogen synthase kinase-3β (GSK) [42].…”
Section: Nutraceuticals: Overviewmentioning
confidence: 99%
See 1 more Smart Citation